2015
DOI: 10.1016/j.hal.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Alexandrium and Scrippsiella cyst viability and cytoplasmic fullness in a 60-cm sediment core from Sequim Bay, WA

Abstract: Many marine protists produce a benthic resting stage during their life history. This non-motile cyst stage can either germinate near the sediment surface to provide the inoculum for subsequent blooms or, be buried by sediment deposits over time and entrained into the sedimentary record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…In studies to date, the number of viable cells generally decreases with sediment depth and age; however some deeper layers had higher numbers (and percentages) of viable cells. Thus Feifel et al (2015) found higher germination percentages of Alexandrium and Scrippsiella at 30-50 cm depth (13-42 years old) than in surface samples; Miyazono et al (2012) found higher concentrations of intact Alexandrium tamarense cysts at 22 cm (ca. 50 years old), although the germination percentage fell linearly with depth and exponentially with age.…”
Section: (B) Dinoflagellatesmentioning
confidence: 91%
See 4 more Smart Citations
“…In studies to date, the number of viable cells generally decreases with sediment depth and age; however some deeper layers had higher numbers (and percentages) of viable cells. Thus Feifel et al (2015) found higher germination percentages of Alexandrium and Scrippsiella at 30-50 cm depth (13-42 years old) than in surface samples; Miyazono et al (2012) found higher concentrations of intact Alexandrium tamarense cysts at 22 cm (ca. 50 years old), although the germination percentage fell linearly with depth and exponentially with age.…”
Section: (B) Dinoflagellatesmentioning
confidence: 91%
“…Thus Feifel et al . () found higher germination percentages of Alexandrium and Scrippsiella at 30–50 cm depth (13–42 years old) than in surface samples; Miyazono et al . () found higher concentrations of intact Alexandrium tamarense cysts at 22 cm ( ca .…”
Section: Phytoplankton Resting Stages and Records Of Their Persistencementioning
confidence: 94%
See 3 more Smart Citations